Electrode fall voltage of arc between deion plates during direct-current interruption period. (7th June 2017) - Yokomizu, Y; Ueda, Y; Matsumura, T; Ichikawa, T; Niwa, Y; Sakaguchi, W
Abstract: A direct-current low-voltage circuit breaker has an arc chute that consists of a stack of several metallic deion plates. The deion plate is also called a splitter plate. The function of the deion plates is to split the arc into several series short-gap arcs. This phenomenon leads to the emergence of electrode fall voltages in the arc chute, eventually contributing to rise in the total arc-voltage in the circuit breaker and to successful current-interruption. The electrode fall voltage therefore plays an important role for successful current-interruption. The present paper describes the estimation result for the electrode fall voltage v e l e of the arc between steel deion plates. The estimation is performed by using a newly devised method. This method utilizes the voltage v c h u t e measured across the arc chute and eventually derives v e l e on the basis of the statistics: a correlation coefficient between an arc-column electric-field strength E c o l and an arc current i . Adopting the devised method enabled us to derive 19 V as v e l e . Verification is furthermore made to show the validity of the determined electrode-fall voltage, 19 V.